EXAMINING OF TEACHERS' PRACTICES SUPPORTED BY MENTORING APPLICATIONS - Alpaslan Şahinoğlu; Ayşegül Sağlam Arslan (Borys Grinchenko Kyiv Metropolitan University, 2023)
The aim of this study is to investigate the impact of mentoring practices designed to support the implementation of the updated physics curriculum on teacher practices. To achieve this objective, a three-stage model utilizing a group mentoring approach was developed, consisting of Preparation (need assessment to identify current teacher status), Realization (mentoring practices addressing identified gaps in subject knowledge), and General Evaluation (assessment of the impact of mentoring practices on teacher practices before, during, and after the implementation process). The didactic engineering method was adopted, and three physics teachers were observed over a 16-week period using camera recordings. The observations were categorized according to physics-specific competencies, and the teachers' practices were analyzed accordingly. The findings indicate that the mentoring support had a positive impact on the teachers' development of didactic structure and student-centered approaches, with some regression observed after the cessation of mentoring. However, teachers' practices remained improved compared to their initial state. This study was limited to three volunteer physics teachers, but the results suggest that mentoring practices can be more effective in improving teachers' compliance with the curriculum in applied teacher education, and the study has practical implications for teacher training and professional development. The study contributes to the field by providing a different perspective on teacher training, emphasizing practical training and needs assessment over theoretical education.